Coming of Age in J. D. Salinger’s The Catcher in the Rye: Eriksonian Psychoanalytic Perspectives - Neimneh, Shadi (Cultural Arts Research and Development, 2025)
This article examines J. D. Salinger’s The Catcher in the Rye (1951) through the psychosocial lens of Erik Erikson’s developmental theory, illustrating the protagonist’s coming-of-age struggles as he transitions from adolescence to early adulthood. Holden Caulfield is portrayed as a teenager in crisis, clinging to the innocence of childhood—a fixation that complicates his individuation and separation from family influences in the formation of own identity. Emotionally unstable and deeply affected by traumatic experiences and the pervasive “phoniness” of his surroundings, Holden finds it difficult to succeed academically or to integrate socially with peers and schoolmates. Using the American psychoanalyst’s psychosocial model on personality development, Erikson’s eight stages chart, and especially the pertinent stages which capture the protagonist’s age, the article seeks to justify Caulfield’s plight and explore possibilities for his redemption and reasons behind his disillusionment. The argument centers on the intersection Erikson describes between two stages: adolescence and early adulthood. Holden’s problems stem from his precarious position on the threshold between these stages, as well as from unresolved childhood attachments and traumas—what Erikson refers to as a “moratorium.” The hypocritical and superficial adult world either seeks to exploit him or further isolates him, exacerbating his sense of alienation. However, his attachments to the memory of his deceased brother, Allie and to the purity embodied by his younger sister, Phoebe, offer him an escape from the ugly realities of the adult world. Overall, Salinger’s book is one of redemption; it is a significant contribution to youth culture and the ethical imperatives of supporting adolescents during their psychosocial development.